Shaping political image through politeness strategies in the presidential debates - Dalimunte, Ahmad Amin; Wen, Fengwei (JEES (Journal of English Educators Society), 2022)
Politeness involves evaluations and attitudes which are closely connected to the assessment of actions. Politeness investigations in presidential debates enables voters to assess the candidates’ behavior to make well-informed decision during the election. The present study investigated politeness strategies in two different presidential debates within the United States electoral context: the Democratic party and the final presidential debates. Data were analyzed by adopting the coding scheme in Brown and Levinson’s frameworks. The overall result indicated that both the presidential debates used more positive politeness strategies than the negative politeness. PPS-10 (offer and promise), PPS-12 (include speaker and hearer in the activity) and NPS-2 (hedge) were more frequently used in both types of debates. PPS-3 (intensify interest to hearer) was frequent in the democratic debate alone. Meanwhile, PPS-15 (give gits to hearer) was frequent in the final presidential debate alone. The findings imply that the use of the politeness strategies can shape the candidates’ positive political images in the presidential debates. HIGHLIGHTS: Findings show that the selected politeness strategies are to shape candidates’ positive political images in the presidential debates. Having positive images such as not harsh, having good behavior are considered to be critical importance in determining the winning of the election. Negative politeness is less preferably used and has been less taken into account as proper rhetorical skills in the debates.